2015
DOI: 10.1007/s10295-015-1647-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving flavor metabolism ofSaccharomyces cerevisiaeby mixed culture withBacillus licheniformisfor ChineseMaotai-flavor liquor making

Abstract: Microbial interactions could impact the metabolic behavior of microbes involved in food fermentation, and therefore they are important for improving food quality. This study investigated the effect of Bacillus licheniformis, the dominant bacteria in the fermentation process of Chinese Maotai-flavor liquor, on the metabolic activity of Saccharomyces cerevisiae. Results indicated that S. cerevisiae inhibited the growth of B. licheniformis in all mixed culture systems and final viable cell count was lower than 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…Antihypertensive activity (Park et al, 2016), production of volatile compounds and organic acids (Meng et al, 2015;Wu & Xu 2012;Yan et al, 2013), production of bioactive substances (Kudryashova et al, 2005;Lee et al, 2008;Ongena & Jacques, 2008)…”
Section: Bacillus Amyloliquefaciensmentioning
confidence: 99%
“…Antihypertensive activity (Park et al, 2016), production of volatile compounds and organic acids (Meng et al, 2015;Wu & Xu 2012;Yan et al, 2013), production of bioactive substances (Kudryashova et al, 2005;Lee et al, 2008;Ongena & Jacques, 2008)…”
Section: Bacillus Amyloliquefaciensmentioning
confidence: 99%
“…The MI groups has a lower relative abundance of Bacillus , possibly due to the competitive relationship between Bacillus and other bacteria for the shared ecological niches (Prosser et al ., ). An alternative reason was that Bacillus might be inhibited by fungi, which would reduce produce ethanol (Meng et al ., ). This phenomenon was also reflected in the B. licheniformis enhanced experiment (Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Research had shown that yeast contributed to the formation of ethyl acetate (Zhang et al ., ; Zha et al ., ); Bacillus licheniformis increased the content of aromatic compounds and pyrazines in Daqu fermentation (Wang et al ., ); Lactobacillus also affected the formation of esters during the Daqu fermentation (Pang et al ., ). Moreover, research revealed that B. licheniformis impacted positively on the metabolic activity of S. cerevisiae , resulting in more ethanol and flavour compounds in mixed culture systems (Meng et al ., ). These findings all illustrated the close relationship between microbial communities, enzymes and volatile compounds.…”
Section: Resultsmentioning
confidence: 97%
“…[20,21] Fermentation is a conventional process of the production of Chinese liquor. [22,23] A large number of literatures reported that fermentation could reduce the pesticide residues. [12,13,24,25] As presented in Table 3, the residues of triadimefon, lambda-cyhalothrin, beta-cypermethrin, esfenvalerate, pyraclostrobins and difenoconazole were lowered by 47%, 59%, 45%, 42%, 37%, and 55% during primary fermentation, and further reduced by 46%, 46%, 38%, 58%, 65%, and 49% in secondary fermentation, separately.…”
Section: Methods Validationmentioning
confidence: 99%